A Fractured and Weaker Public Service Media: Territorial Organisation, Public Media Policy and Economic Crisis in Spain - Guimerà Orts, Josep Àngel; Bonet, Montse (Javnost-The Public, 2020)
The economic crisis that began in 2008 has brought to the table the unstructured nature of the Spanish public broadcasting system. In Spain, the Public Service Media is organised into three almost watertight territorial levels that do not collaborate with each other, and even sometimes compete for the same resources. In addition, the different political elites (local, regional and national) see their media as their own, and those of the other administrations as opponents. This division, which we call a geographic-administrative fracture, has prevented a global management of the system, which has led to more consequences other than merely economic ones. This article provides a novel vision of the (permanent) crisis of the Spanish public media, highlighting a defining characteristic of the system, hardly ever considered as a key factor in its (bad) functioning: territorial division.